MacArthur's coalition US and Australian operations in the Southwest Pacific area, 1942-1945 - Dean, Peter J. (Peter John) 1974- (Lawrence University Press of Kansas, 2018)
"From 1942-1945 the Allies' war in the Southwest Pacific was effectively a bilateral coalition between the United States and Australia under the command of General Douglas MacArthur. By charting the evolution of the military effectiveness of the US-Australian alliance, MacArthur's Coalition puts the relationship between the United States and Australia at the center of the war against Japan. Drawing on new primary source material, Peter J. Dean has written the first substantial book-length treatment of the coalition as a combined military force. This expansive and ambitious book provides a fresh perspective on the Pacific War by providing a close-up, in-depth account of operations in the Southwest Pacific from the Kokoda Trail campaign to the reconquest of the Philippines and Borneo. Dean's work takes the reader deep into the key military headquarters in the Southwest Pacific and reveals the discussions, debates, and arguments between key commanders and staff officers during the course of planning and waging a monumental conflict. Drawing upon archival records across three continents, Dean brings the qualities of these senior officers to life by exploring the critical importance of personalities and leadership in overcoming cultural, doctrinal, and organizational divides in the largely unequal alliance. Set against the practicalities of fighting a fanatical enemy in some of the most inhospitable terrain in the war, his book shows how, despite these divides and MacArthur's difficult personality, the US-Australian coalition was able to forge a highly effective and ultimately triumphant fighting machine. With its unprecedented view of the joint nature of operations in the Southwest Pacific and its focus on frontline commanders and units in forging a successful fighting force, MacArthur's Coalition illuminates a critical aspect of the Allied victory in World War II. "
"From 1942-1945 the war in the Pacific was divided into two major theatres: the Pacific Oceans Area (POA) under the command of Admiral Chester Nimitz (US Navy) and the Southwest Pacific Area (SWPA) under the command of General Douglas MacArthur (US Army). The POA was fundamentally an all-US command, while at the heart of the SWPA laid a coalition of allies: the United States, Australia, and the Netherlands. Under Nazi occupation and with their forces in the Far East largely destroyed in the first months of the Pacific War, the Dutch were only able to play a very minor role in the SWPA. MacArthur's coalition was, therefore, principally a bilateral one between the United States and Australia. This book is about that military partnership. Peter Dean asks three key questions: 1. Why did Allied strategy lead to the creation of the SWPA? How was this military theatre organized? 2. How did the coalition in the SWPA operate on the battlefield? 3. What where the stresses, strains, and areas of success for this coalition?"
Includes bibliographical references and index.
Keywords: MacArthur, Douglas -- 1880-1964.; Allied Forces. -- South West Pacific Area; World War, 1939-1945 -- Pacific Area; World War, 1939-1945 -- Australia; World War, 1939-1945 -- United States; World War, 1939-1945 -- Campaigns -- Philippines; World War, 1939-1945 -- Campaigns -- Pacific Area; Theater of war; United States -- Military relations -- Australia; Australia -- Military relations -- United States